2022
DOI: 10.3390/pathogens11101101
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in an Aging World

Abstract: Tuberculosis (TB) is one of the leading causes of death due to its being an infectious disease, caused by the airborne pathogen Mycobacterium tuberculosis (M.tb). Approximately one-fourth of the world’s population is infected with latent M.tb, and TB is considered a global threat killing over 4000 people every day. The risk of TB susceptibility and mortality is significantly increased in individuals aged 65 and older, confirming that the elderly represent one of the largest reservoirs for M.tb infection. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 124 publications
0
14
0
1
Order By: Relevance
“…In this study, we found that the YLLs were the predominant contributor to the PTB DALYs in Shenyang in 2023, accounting for about 71.38%, which was consistent with the ndings in China [10] , Brazil [32] , and India [33] . It suggested that PTB was more likely to lead to premature death rather than disability, possibly due to its older age of onset [34] , high drug resistance, and a higher rate of delayed diagnosis (64.54%) [31,35] . Therefore, the focus should be shifted towards early intervention to reduce transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the YLLs were the predominant contributor to the PTB DALYs in Shenyang in 2023, accounting for about 71.38%, which was consistent with the ndings in China [10] , Brazil [32] , and India [33] . It suggested that PTB was more likely to lead to premature death rather than disability, possibly due to its older age of onset [34] , high drug resistance, and a higher rate of delayed diagnosis (64.54%) [31,35] . Therefore, the focus should be shifted towards early intervention to reduce transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The seventh census of China showed that the population over 65 years old accounted for 13.5% of the total population [ 37 , 38 ]. The elderly is prone to TB than the younger due to weakened immune system, insufficient nutrient intake, high incidence of chronic diseases, and high prevalence of bad habits (such as smoking and alcohol consumption) [ 3 , 39 ]. Once infected with TB, the elderly is prone to respiratory complications (e.g., pulmonary infections and COPD) and pathological changes (e.g., lung tissue injury and bronchial dilatation), making TB treatment more difficult [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…60 Jahren) etwas häufiger vorkommt [3]. Bedingt durch die Beeinträchtigung insbesondere der zellulären Immunität im höheren Lebensalter, dem Vorliegen weiterer Grunderkrankungen und Behandlungen, Unterernährung, gemeinsamer Benutzung der Einrichtungsräumlichkeiten ("enger Raum") und andere Faktoren gehören die meist älteren Bewohnerinnen und Bewohner von Pflegeheimen zu einer Population mit erhöhtem Risiko für eine Tuberkulose [84,85]. Im Allgemeinen tritt im Seniorenalter die Tuberkulose in Form einer Reaktivierung einer früher akquirierten Infektion auf, aber auch exogene (Re-)Infektionen sind möglich.…”
Section: Pflegeeinrichtungen Und Teilstationäre Einrichtungenunclassified